Effectiveness of Iron Oxide Nanoparticles for MR Imaging and Tissue Ablation - Saeed, Maythem; Wilson, Mark W. (Current Nanomedicine, 2018)
Background: The introduction of new less invasive and non-invasive techniques for treating cardiac arrhythmias and neoplastic tissues has enhanced interest in medical imaging and iron oxide nanoparticles. The main scope of this review is to provide an overview on the usage of iron oxide nanoparticles (IONP) in magnetic resonance imaging (MRI) and thermal ablation. Methods: Several methods have been proposed to ablate abnormal growth and myocardial arrhythmia; namely surgical, radiofrequency, chemical and cryoablation. Fluoroscopy, multi-detector computed tomography, MRI as well as ultrasound are currently used for diagnosis and guiding therapies. Image-guided techniques help in visualizing the targets, precise delivering/verifying the treatment and follow up the prognosis. Results: Over one hundred papers were included in this review; the majority of the papers addressed the unique features of IONP and MRI settings. IONP have attracted special interest in MRI and thermal ablation due to their high relaxivity, biocompatibility, magnetic heating and low toxicity. The concept of ablation by magnetic nanoparticles is based on depositing magnetic nanoparticles in the tumor and their subsequent heating by an external alternating magnetic field. IONP have been used as: 1) MR contrast media for visualizing pathologic lesions before, during, and after ablation, 2) hyperthermal agents for generating heat during exposure to alternating magnetic field and 3) magnetic vectors (drugs and gene carriers) guided by magnetic field gradients to deliver therapies to pathologic lesions. IONP highlight ablated lesions in neighboring healthy tissue or organs due to improper targeting of lesions. It also enhances the vascular tree for proper catheter navigation. Conclusion: Iron oxide nanoparticles incorporate good biocompatibility and safety margin with their unique magnetic and thermic properties. IONP can be delivered locally and systemically (with caution). Furthermore, they blend diagnosis and treatment. The provision of pre-, during and post-ablation lesion characterization on IONP-contrast enhanced MRI might be helpful in complex ablation procedures and treatment.
Keywords: tumors